Coronavirus, Demons, and War: Visual and Multimodal Metaphor in Chinese Public Service Advertisements. (February 2022) - Feng, Debing; Wu, Xiangxiang
Metaphors in public service advertisements, or PSAs, have played an important role in promoting the knowledge of COVID-19 and China's anti-epidemic activities. Based primarily on Feng and O'Halloran's visual representation of multimodal metaphor, this article examines visual and multimodal metaphors created in the online PSAs that were produced in early 2020 to publicize China's epidemic prevention and control activities. It is found that those metaphors fall into three general groups, namely "coronavirus" metaphor, "anti-epidemic worker" metaphor, and "medical instrument" metaphor. Nearly all of them were created to serve an overarching metaphor, namely ANTI-EPIDEMIC WORK IS WAR, of which coronaviruses were depicted as enemies, anti-epidemic workers as warriors, and medical instruments as weapons. Most of the metaphors were constructed through visual or multimodal anomaly realized through strategies such as participant substitution, verbal/visual superimposition, and verbo-visual integration/fusion in the representational structure, while their metaphorical meanings became supplemented or reinforced by the deployment of compositional and interactive resources such as spatial position, color contrast, gaze, and size. Finally, the causes and implications of the findings are discussed from three aspects: social background, genre, and audience.